Implementing the Merdeka Curriculum in Islamic Cultural History Instruction to Enhance Student Collaboration: A Case Study of Grade 7 at MTs Al-Iman Unit 2 Tulang Bawang - Mariyatul Kiptiyah; Miswanto Miswanto; Sri Hadayani (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
This study explores the implementation of the Independent Learning Curriculum (Kurikulum Merdeka Belajar, KMB) in the Islamic Cultural History (SKI) subject as a medium to develop collaborative learning among seventh-grade students at MTs Al-Iman Unit 2 Tulang Bawang. Employing a qualitative descriptive approach with a case study method, data were gathered through classroom observations, in-depth interviews with teachers and students, and analysis of instructional documents. The findings indicate that KMB principles have been adopted effectively in SKI instruction by utilizing student-centered learning, active methodologies, and varied media. Collaborative strategies such as group discussions, project-based learning, and peer-assisted learning were visibly employed, resulting in increased student engagement, improved critical thinking and communication skills, and strengthened responsibility among learners. These outcomes reflect the integration of 21st-century skills within religious education and align with the broader vision of the “Profil Pelajar Pancasila.” The study concludes that the successful integration of KMB in SKI learning contributes not only to academic outcomes but also to character formation and interpersonal competence. It recommends continued teacher training, increased access to diverse learning resources, and improved evaluation frameworks to sustain and scale collaborative learning in Islamic education settings.